Dampak Dukungan Keluarga terhadap Keberhasilan PKBM dalam Menurunkan Angka Putus Sekolah di Kabupaten Enrekang - Risman; Arsyad Genda; Mansyur Rajab (Mataram University, 2026)
The high school dropout rate remains a challenge in educational development in Indonesia, including in Enrekang Regency. In this context, Community Learning Centers (PKBM) serve as an alternative education for those unable to complete formal education. This study aims to analyze the impact of family support on the success of PKBM in reducing the dropout rate at PKBM Melati, Enrekang Regency. The study used a qualitative approach with a case study type. Research informants consisted of PKBM managers, tutors, learners, and families of learners who were selected purposively. Data were collected through in-depth interviews, observation, and documentation, then analyzed using the interactive analysis model of Miles, Huberman, and Saldana. The results showed that family support is a crucial factor in supporting learners' success in participating in the equivalency education program. The forms of support found included emotional support, instrumental support, and social support, with emotional support being the most dominant form. This support contributes to increased learning motivation, participation in learning activities, and the sustainability of learners' education. This study also found that family economic constraints, low parental education levels, and stigma against non-formal education are the main obstacles to optimizing family support. The research findings confirm that the success of PKBM in reducing the risk of dropping out of school is not only determined by the quality of the educational program, but also by the involvement of the family as the closest social environment of the learners.